2021
DOI: 10.1002/aocs.12477
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Oil and Nonthermal Plasma Pretreatment to Dye Para‐Aramid Woven Fabrics with Disperse Dye Using a Glycerol‐Based Dye Bath

Abstract: High-performance para-aramid fibers offer a number of uses as strong, lightweight materials for protective vests, helmets, tires, and other applications. The chemically inert nature of the fibers makes them difficult to dye or durably print by conventional dyeing techniques for textiles, and solution dyeing during production of the fibers can limit the color of para-aramid fabrics to the color of the spun yarn prior to weaving or knitting and thereby limit the practical applications of these textiles as protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 28 publications
2
15
1
Order By: Relevance
“…TWEEN was the only factor not involved in any significant interactions; the addition of the surfactant negatively affected dyeing performance, consistent with our previous observations [ 9 , 10 ]. The surfactant, although helping to form a dye dispersion, might also hinder the diffusion of the dye onto the para-aramid fiber fabrics.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…TWEEN was the only factor not involved in any significant interactions; the addition of the surfactant negatively affected dyeing performance, consistent with our previous observations [ 9 , 10 ]. The surfactant, although helping to form a dye dispersion, might also hinder the diffusion of the dye onto the para-aramid fiber fabrics.…”
Section: Resultssupporting
confidence: 91%
“…The para-aramid fabrics used in this study are made of tightly woven 300 Denier continuous filament and were provided by the U.S. Army Development Command—Soldier Center (Natick, MA, USA). This highly crystalline material has been proven undyeable by conventional methods using either a cationic dye or a disperse dye, even with nonthermal plasma surface treatment, but were dyed using soybean oil/NTP pretreatments [ 9 , 10 ]. Blue cationic dye (Victoria Blue R, CAS Number 2185-86-6), Disperse Red 1 acrylate dye (CAS Number 13695-46-0), AESO (CAS Number 91722-14-4), acrylic acid (CAS Number 79-10-7), and ethyl acetate (CAS Number 141-78-6) were purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purposes of providing a visual demonstration comparing the dyeing strengths of different treatments, select samples were imaged using a flatbed scanner ( Figure 8 ). Compared with the previous investigation of dyeing para-aramids with this method and using a disperse dye [ 27 ], it is demonstrated that the pretreatment of soybean oil followed by NTP treatment method is compatible with dyeing with both disperse dye and cationic dye. Further, this method enables dyeing to a significantly high color strength, although the disperse dye requires glycerol as a dispersant, but water as the solvent is better suited for the use of cationic dye.…”
Section: Resultsmentioning
confidence: 91%
“…The SDBD system has been described previously for dyeing with a disperse dye [ 27 ] and is summarized here. The SDBD apparatus uses ambient air as the feed gas and comprises two electrodes that are separated by an alumina dielectric plate (dimensions = 108 × 95 × 1 mm 3 thick) and powered by a high voltage power source with a sinusoidal high voltage of 9.2 kV that was tuned to a 23.2 kHz resonance frequency (see Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%